Pembukuan dan pelaporan keuangan sederhana untuk umkm pada komunitas umkm depok - Abriandi Abriandi; Imam Suryono (LPMP Imperium, 2023)
This activity aims to increase the understanding and knowledge of Micro, Small and Medium Enterprises actors in carrying out simple bookkeeping and financial reporting for their businesses. So that MSME actors can better manage their business bookkeeping and financial reporting. Participants are given training activities using the classical method, namely the delivery of training material through lectures, then followed by a questions and answers session as well as discussions and exercises/practices; giving papers filled in accordance with the real conditions of the participants' businesses. Participants in the training activities were Micro, Small and Medium Enterprises located in Depok. This training activity was attended by all participants with enthusiasm because it provided many benefits for the continuity of their business.